Depositional conditions on an alluvial fan at the turn of the Weichselian to the Holocene – a case study in the Żmigród Basin, southwest Poland - Zieliński, Paweł; Sokołowski, Robert J.; Fedorowicz, Stanisław; Woronko, Barbara; Hołub, Beata; Jankowski, Michał; Kuc, Michał; Tracz, Michał (Geologos, 2016)
Presented are the results of research into the fluvio-aeolian sedimentary succession at the site of Postolin in the Żmigród Basin, southwest Poland. Based on lithofacies analysis, textural analysis, Thermoluminescence and Infrared-Optical Stimulated Luminescence dating and GIS analysis, three lithofacies units were recognised and their stratigraphic succession identified: 1) the lower unit was deposited during the Pleni-Weichselian within a sand-bed braided river functioning under permafrost conditions within the central part of the alluvial fan; 2) the middle unit is the result of aeolian deposition and fluvial redeposition on the surface of the fan during long-term permafrost and progressive decrease of humidity of the climate at the turn of the Pleni- to the Late Weichselian; 3) the upper unit accumulated following the development of longitudinal dunes at the turn of the Late Weichselian to the Holocene; the development of dunes was interrupted twice by the form being stabilised by vegetation and soil development.